Theory of morphology and morphology in action: main aspects - Bieliayeva, O.Yu. (ХНУ ім. В.Н. Каразіна, 2016)
The article deals with the problems of morphology. Morphological facts of everyday life are studied from the point of view of its use in a human speech. The conclusion is made that morphology is connected not only with scientific approaches to the language, but with every day use of it.
Keywords: generative grammar; lexicon; linguistics level; morphology; phonology; syntax